Applications of p-n homojunction ZnO nanowires to one-diode one-memristor RRAM arrays. (October 2020) - Chen, Jui-Yuan; Wu, Min-Ci; Ting, Yi-Hsin; Lee, Wei-Che; Yeh, Ping-Hung; Wu, Wen-Wei
Abstract: Nanowire (NW) structure is superior at defining the direction of device due to its one-dimension feature. In this work, the p-n ZnO NWs were successfully synthesized, and were able to vertically grow on Ta2 O5 substrate. Thus, the well-performed Au/p-n ZnO NWs/Ta2 O5 /Au one-diode one-memoristor device was fabricated. The p-n ZnO NWs not only exhibited excellent rectifying behavior, but also played the role of oxygen storing during filaments formation. Therefore, the low-leakage device aimed to build high-density crossbar arrays which was required for accelerating the combination of 5 G with AI in near future applications. Graphical abstract: ToC: The p-n ZnO nanowires can directly grow on Ta2 O5 substrate by the hydrothermal method. In the Au/p-n NWs/Ta2 O5 /Au device, the p-n ZnO NWs not only formed an asymmetric barrier to restricted the sneak flow, but also aimed to supply the oxygen vacancies source for Ta2 O5 thin film layer during forming and set process. Image, graphical abstract